Fractional Order Control System - Singh, Swati; Kosti, Ankita (International Journal of Emerging Trends in Science and Technology, 2014)
Abstract: This paper includes the study of fractional order PID control system. In this firstly the study of step input signal in time domain for getting transient response using normal control system is done. Then with the use of fractional order syetem same analysis is done and the two resuls are being compared. With the use of fractional order control system, improved response is obtained.